STORYNOMICS DESA WISATA: PROMOSI DESA WISATA MUNGGU BERBASIS NARASI STORYTELLING - Ni Nyoman Arini; I Wayan Putra Aditya; I Wayan Kartimin; I Putu Tiana Raditya (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
Storynomics tourism is one of the strategies in promoting tourism, especially rural tourism. The cultural heritage in Munggu Tourism Village has historical stories and cultural values that are still believed by the local community, so the concept of storynomics tourism can be developed in promoting digital-based rural tourism by still maintaining local wisdom in the form of verbal traditions. The storynomics concept of Munggu Tourism Village is a form of promotion of digital storytelling-based rural tourism with the concept of storytelling in a creative content in which there is a concise description of verbal traditions in two language versions, that are bahasa Indonesia and English. This study analyzed the storynomics tourism which is directed as a new way to promote the uniqueness of tourist attractions in Munggu Tourism Village by telling verbal traditions including the history and cultural values of the local wisdom contained therein. The relevant research approach used in this study is a qualitative approach. The theory used in this research is storynomics tourism. This study concludes that Munggu Tourism Village has natural and cultural tourist attractions that keep the history and verbal traditions that have been believed by the local community for generations. Natural and cultural tourist attractions in the Munggu Tourism Village which are narrated for the promotion needs of the Munggu Tourism Village are The Tradition of Mekotek, The Traditional Swing, Munggu Beach, and Pancoran Pule, as well as the creative economy, namely Balinese traditional foods and paintings.